Excess Properties of Binary Mixtures of 2-Propanol and 3-Pentanone with p-Xylene at Different Temperatures - Rattan, V.K.; Singh, Sukhmehar; Katyal, R.C.; Kapoor, Seema; Gupta, Geetanjali (Asian Journal of Chemistry, 2016)
The viscosities, densities and speeds of sound for binary mixtures of 2-propanol with p-xylene at 293.15 and 313.15 K and 3-pentanone with p-xylene at 293.15, 303.15 and 313.15 K have been measured over the whole compositional range. The excess thermodynamic properties such as excess volume (VE), excess compressibility (KSE) and deviations in viscosity (Dh) were calculated.